Isolation of anti-angiogenesis antibodies from a large combinatorial repertoire by colony filter screening - Giovannoni, Leonardo (Oxford University Press, 2001)
We describe here a method, based on iterative colony filter screening, for the rapid isolation of binding specificities from a large synthetic repertoire of human antibody fragments in single-chain Fv configuration. Escherichia coli cells, expressing the library of antibody fragments, are grown on a porous master filter, in contact with a second filter coated with the antigen, onto which antibodies secreted by the bacteria are able to diffuse. Detection of antigen binding on the second filter allows the recovery of a number of E.coli cells, including those expressing the binding specificity of interest, which can be submitted to a second round of screening for the isolation of specific monoclonal antibodies. We tested the methodology using as antigen the ED-B domain of fibronectin, a marker of angiogenesis. From an antibody library of 7 × 10(8) clones, we recovered a number of specifically-binding antibodies of different aminoacid sequence. The antibody clone showing the strongest enzyme-linked immunosorbent assay signal (ME4C) was further characterised. Its epitope on the ED-B domain was mapped using the SPOT synthesis method, which uses a set of decapeptides spanning the antigen sequence synthesised and anchored on cellulose. ME4C binds to the ED-B domain with a dissociation constant K(d) = 1 × 10(–7) M and specifically stains tumour blood vessels, as shown by immunohistochemical analysis on tumour sections of human and murine origin.